Effect of plasma beta on the nonlinear evolution of m/n = 2/1 double tearing mode in high Lundquist number regime - Dingzong Zhang; Zhaoqing Wu; Jun Ma; Wenfeng Guo; Yanqing Huang; Hongbo Liu (Nuclear Fusion)
The existing results indicate that in the large Lundquist number regime, plasmoids play an important role in the growth and saturation of the double tearing mode (DTM). In this paper, the effect of plasma beta on the nonlinear evolution of the m / n = 2/1 DTM in large Lundquist number regime is numerically investigated in a cylinder geometry. The results demonstrate that the impact of plasma beta on plasmoid dynamics varies significantly with the separation distance between rational surfaces. In the small separation regime ( $Δ r = 0.1$ ), no plasmoids are observed, regardless of plasma beta and resistivity. However, when the separation is relatively large ( $Δ r = 0.2$ or $Δ r = 0.3$ ), plasmoids exhibit highly complex behavior under different plasma beta and resistivity conditions. For the medium separation $Δ r = 0.2$ , the resistivity threshold for the emergence of plasmoids is approximately $2.5 × {10^{ - 6}}$ and is not affected by plasma beta. Conversely, when the separation increases to $Δ r = 0.3$ , the resistivity threshold is significantly influenced by plasma beta. Under certain conditions, this threshold can reach as high as $1.0 × {10^{ - 5}}$ , which is much higher than the typical value of around ${10^{ - 7}}$ . Furthermore, a preliminary case study shows that the tokamak plasma rotation shear has a significant impact on plasmoid dynamic.